Cancer odds among Ohio firefighters: data from the Ohio Cancer Incidence Surveillance System (OCISS) 1996–2019 - Robert Hood; Olorunfemi Adetona; Susan Elizabeth Olivo-Marston; Shashank Singh (BMJ Public Health)
Objectives The objective of the current case–control study was to examine the odds of cancer among firefighters in the state of Ohio and compare the odds of being a firefighter versus police or the general population across different cancer types.Methods Cancer cases were examined from the Ohio Cancer Incidence Surveillance System (OCISS) between 1996 and 2019. Occupation status was classified as firefighter, police or general population. Logistic regression models were run to calculate ORs to determine the odds of being a firefighter compared with police or the general population across different cancer types. Models were adjusted for gender, race, age at cancer diagnosis and year of cancer diagnosis.Results Among the 906 164 cancer cases, 3397 were firefighters and 3341 were police. Firefighters were more likely to be men, white, non-Hispanic, married and a mean age of 66 at the time of cancer diagnosis. Firefighters had increased odds of cancer of the brain (OR=1.40, 95% CI: 0.99 to 1.99) and thyroid (OR=1.53, 95% CI: 1.05 to 2.23) compared with police and oesophageal (OR=1.83, 95% CI: 1.43 to 2.33), skin (OR=1.23, 95% CI: 1.06 to 1.42), brain (OR=1.37, 95% CI: 1.08 to 1.73) and thyroid (OR=1.52, 95% CI: 1.18 to 1.96) compared with the general population. They had decreased odds of pancreas, lung and bronchus and bladder compared with both police and the general population. Similar patterns were observed among male firefighters.Conclusions The current study demonstrated increased odds of several different types of cancer among Ohio firefighters compared with other individuals within the OCISS, which may be associated with differences in risk factors, including occupational exposures. The results align with evidence that firefighting is a cancer risk factor. This study is strengthened by the ability to also compare firefighters to police with regards to the odds of cancer. This supports future hypothesis-driven studies examining how specific occupational exposures are associated with increased cancer risk among Ohio firefighters.